An assessment of burn injury hospitalisations of adolescents and young adults in Western Australia, 1983-2008 - Duke, Janine; Wood, Fiona; Semmens, James; Edgar, D.; Spilsbury, Katrina; Rea, S. (Elsevier, 2012)
Background: This study presents a 26-year epidemiological assessment of burn injury hospitalisations for people 15–29 years of age in Western Australia. Methods: Linked hospital morbidity and death data for all persons hospitalised with an index burn injury in Western Australia for the period 1983–2008 were analyzed. Annual age-specific incidence rates were estimated. Poisson regression analyses were used to estimate temporal trends in hospital admissions. Results: There were 6404 burn hospital admissions of which 76% were male. Males had hospitalisation rates 3.0 times that of females (95%CI: 2.8–3.2) and Aboriginal people had rates 2.3 times (95%CI: 2.1–2.5) that of non-Aboriginal persons. Hospitalisations for burn injury declined by 42% (95%CI: 35–47) for males and 21% (95%CI: 6–33) for females. Hospitalisations declined by 53% (95%CI: 35–63) for Aboriginal people, and by 35% (95%CI: 29–41) for non-Aboriginal people. Significant reductions were observed for flame and electrical burn hospitalisations. The major causes of burns in males were exposure to controlled fires and ignition of inflammable materials, with scalds the predominant cause of burn in females. Conclusions: Downward trends in burn injury hospitalisations for both males and females 15–29 years of age were observed; however, males and Aboriginal persons have significantly elevated hospitalisation rates.